Induced Expression of kir6.2 in A1 Astrocytes Propagates Inflammatory Neurodegeneration via Drp1-dependent Mitochondrial Fission - Song, Nanshan; Zhu, Hong; Xu, Rong; Liu, Jiaqi; Fang, Yinquan; Zhang, Jing; Ding, Jianhua; Hu, Gang; Lu, Ming (Frontiers in Pharmacology, 2021)
Glia-mediated inflammatory processes are crucial in the pathogenesis of Parkinson’s disease (PD). As the most abundant cells of the brain and active participants in neuroinflammatory responses, astrocytes largely propagate inflammatory signals and amplify neuronal loss. Hence, intensive control of astrocytic activation is necessary to prevent neurodegeneration. In this study, we report that the astrocytic kir6.2, as a abnormal response after inflammatory stimuli, promotes the reactivity of A1 neurotoxic astrocytes. Using kir6.2 knockout (KO) mice, we find reversal effects of kir6.2 deficiency on A1-like astrocyte activation and death of dopaminergic neurons in lipopolysaccharide (LPS)-induced mouse models for PD. Further in vitro experiments show that aberrant kir6.2 expression induced by inflammatory irritants in astrocytes mediates the dynamin-related protein 1 (Drp1)-dependent excessive mitochondrial fragmentation and results in mitochondrial malfunctions. By deleting kir6.2, astrocytic activation is reduced and astrocytes-derived neuronal injury is prevented. We therefore conclude that astrocytic kir6.2 can potentially elucidate the pathology of PD and promote the development of therapeutic strategies for PD.